Ge-based MAX-phase metal ceramic as well as preparation method and application thereof
By doping Ti, Cr, Mo, and V at the M site, Ge-based MAX phase cermets were prepared, solving the problem of insufficient research on A-site elements other main group elements. This improved the high-temperature mechanical properties and made them suitable for high-temperature conductive ceramics and low expansion coefficient materials.
Patent Information
- Application Number
- CN202510855063.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-11-21
AI Technical Summary
In existing research on MAX phase materials, there are many studies on the A-site of Al in the 413-type MAX phase, but fewer studies on the A-site of other main group elements, especially Ge-based MAX phases, and their high-temperature mechanical properties need to be improved.
Ge-based MAX phase cermets were prepared by doping Ti, Cr, Mo, and V elements at the M site. Ge-based MAX phase cermets with alternating stacked structures were obtained by solid-state sintering and spark plasma sintering methods.
The prepared Ge-based MAX phase cermets possess excellent mechanical properties such as low thermal expansion coefficient, high bulk modulus, and high elastic modulus, making them suitable for high-temperature conductive ceramics and low expansion coefficient materials, with broad application prospects.
Smart Images

Figure CN120987654A_ABST
Abstract
Description
Technical Field
[0001] This application relates to a Ge-based MAX phase cermet, its preparation method, and its application, belonging to the field of functional ceramics. Background Technology
[0002] MAX phases are layered materials composed of early transition metals (M), group a elements (a), and either carbon (C) or nitrogen (N). The molecular formula of MAX phase materials is usually represented as M. n+1 AX n Because of its unique crystal structure of alternating stacked MX and A layers, it combines the excellent characteristics of both metal and ceramic materials.
[0003] Its development history can be traced back to the 1960s. In 1960, Helga Rohde and Hans Kudielka reported the first MAX phases, Ti₂SC and Zr₂SC, thus opening the door to research on MAX phase family materials. The following decade was a fruitful one for the MAX phase family. Crystallologists such as Nowotny discovered about 50 ternary layered compounds with the same structure, naming them the M₂BX or H phase. In 1967, Nowotny's team discovered two new MAX phases, Ti₃GeC₂ and Ti₃SiC₂, further expanding the MAX phase family and breaking the limitations of the M₂AX phase. However, for a long period afterward, research on MAX phase materials entered a period of stagnation. Until 1996, Barsoum et al. synthesized high-purity and highly dense Ti3SiC2 bulk materials through hot pressing at 1600℃. They found that this material had a density comparable to Ti metal, but its hardness (325 GPa) was approximately three times that of Ti metal, and its electrical and thermal conductivity were more than twice that of Ti metal. Therefore, this type of ternary layered compound attracted widespread attention from academia and industry. In 1999, the first MAX phase, Ti4AlN3, was discovered, with n=3, and its space group was consistent with previously reported MAX phases (P63 / mmc). In 2000, Basoum et al. summarized this series of materials previously reported by Nowotny et al., and represented them with the molecular formula Mn+1AXn, where n can usually be represented by 1, 2, or 3, M represents a transition metal, A is a main group element, and X is C / N. The MAX phase material is thus named. MAX phase materials typically possess excellent electrical and thermal conductivity, machinability, low coefficient of thermal expansion, high bulk modulus and elastic modulus, as well as good resistance to oxidation and corrosion, and resistance to friction and wear. This gives them broad application prospects, such as in the fields of electrode and brush materials, high-temperature structural materials, high-temperature heating materials, and chemical anti-corrosion materials.
[0004] Since 1996, researchers have made significant progress in understanding the properties of MAX phases, especially after 2018, with the discovery of over 340 new MAX phases. However, past research on MAX phases has primarily focused on types 211 and 312. Less research has been done on the n=3 type 413 MAX phase, but compared to types 211 and 312, it exhibits more MX layers and better high-temperature mechanical properties. For example, Nb4AlC3 retains 79% of its room-temperature Young's modulus (241 GPa) at 1580 °C, and its flexural strength at 1400 °C shows no decrease compared to room temperature (230 MPa). Ta4AlC3 exhibits high damage resistance and excellent thermal shock resistance. Therefore, the type 413 MAX phase is the most promising in the MAX family for application in ultra-high-temperature structural components. Furthermore, among the currently reported type 413 MAX phases, those with Al at the A-site are predominant. MAX phases with other main group elements at the A-site are less frequently reported. Summary of the Invention
[0005] The purpose of this invention is to provide a novel Ge-based MAX phase with the molecular formula M4AX3, and to provide a method for preparing this MAX phase, through which a new Ge-based MAX phase was obtained for the first time. The new 413-type Ge-based MAX phase material was prepared by elemental doping at the M site, and its structure was analyzed by spherical aberration electron microscopy, X-ray diffraction, and Rietveld refinement. Its thermal expansion and thermoelectric properties were also investigated.
[0006] According to the first aspect of this application, a Ge-based MAX phase cermet is provided. This material, due to its unique crystal structure of alternating MX and A layers, combines the excellent characteristics of both metals and ceramics. It possesses excellent mechanical and thermodynamic properties, including a low coefficient of thermal expansion, high bulk modulus, and high elastic modulus.
[0007] A Ge-based MAX phase cermet, wherein the molecular formula of the Ge-based MAX phase cermet is M4AX3;
[0008] A represents the element Ge, and X represents the element C.
[0009] M is a transition metal element, composed of Ti and Cr elements;
[0010] or
[0011] M is composed of Ti, Cr, and Mo elements;
[0012] or
[0013] M is composed of Ti, Cr, V, and Mo elements.
[0014] Optionally, the elements in M are in equal proportions.
[0015] Optionally, the Ge-based MAX phase cermet is the 413 phase of the MAX phase system.
[0016] Optionally, the Ge-based MAX phase cermet has a hexagonal crystal structure with a space group of P63 / mmc, and the unit cell is composed of three layers of M6X octahedral layers and a single layer of MA triangular prism layers stacked alternately.
[0017] The M position of a metallic element has two atomic positions, namely M1 and M2, which correspond to Wyckoff positions 4a and 4f. Among them, the metallic elements Ti and Cr form ordered atomic occupancy, occupying the M2 and M1 atomic positions respectively.
[0018] In the crystal structure of Ge-based MAX phase cermet materials, one X atom is octahedral coordinated with six M atoms, and one A atom is triangular prism coordinated with six M atoms. Therefore, we can consider its crystal structure as an alternating arrangement of MX layers composed of M6X octahedra connected by common edges and MA layers composed of M6A triangular prisms connected by common edges, with the layers connected by common edges. Because it has more MX layers, it can exhibit better high-temperature mechanical properties.
[0019] Optionally, the molecular formula of the Ge-based MAX phase cermet is as follows:
[0020] (Ti 0.5 Cr 0.5 )4GeC3
[0021] or
[0022] (Ti 1 / 3 Cr 1 / 3 Mo 1 / 3 )4GeC3
[0023] or
[0024] (Ti 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC3.
[0025] According to a second aspect of this application, a method for preparing the Ge-based MAX phase cermet described above is provided. This preparation method is a solid-state sintering method, which is simple to implement, yields high-purity products, and does not require large-scale equipment.
[0026] The preparation method of the Ge-based MAX phase cermet described above includes the following steps:
[0027] S1. Weigh the M element powder, Ge element powder and graphite powder in a molar ratio of 4:1:3 and grind them evenly.
[0028] S2. The uniformly ground powder is cold-pressed into sheets, calcined in an inactive atmosphere, and cooled to room temperature to obtain the Ge-based MAX phase metal ceramic.
[0029] Optionally, in the M element powder, the molar ratio of each element powder is equal.
[0030] Optionally, the calcination conditions are as follows: heating to 900-1100℃ for 150-250 minutes, then heating to 1550-1700℃ for another 150-250 minutes, and holding at that temperature for 200-300 minutes.
[0031] Optionally, after calcination, the material is cooled to room temperature at a cooling rate of less than 5°C / min.
[0032] Optionally, after calcination, the temperature is lowered to 350-450°C in 100-150 minutes, and then allowed to cool naturally to room temperature.
[0033] Specifically, the temperature is raised to 1000°C over 200 minutes, then raised to 1650°C over another 200 minutes, held for 240 minutes, and then cooled to room temperature at a rate not exceeding 5°C per minute.
[0034] Optionally, the following steps are also included:
[0035] S3. Grind the Ge-based MAX phase metal ceramic obtained in step S2 into powder, and perform discharge plasma sintering to obtain Ge-based MAX phase metal ceramic bulk material.
[0036] Optionally, the conditions for the discharge plasma sintering are: a sintering temperature of 1200–1400°C, a sintering time of 8–15 min, and an axial pressure of 30–40 MPa.
[0037] Specifically, the conditions for the discharge plasma sintering are: a sintering temperature of 1300℃, a sintering time of 10 min, and an axial pressure of 35 MPa.
[0038] According to a third aspect of this application, an application of the aforementioned Ge-based MAX phase cermet is provided.
[0039] The above-described Ge-based MAX phase cermets and the Ge-based MAX phase cermets prepared by the above-described preparation method are used in high-temperature conductive ceramic materials and low expansion coefficient materials.
[0040] The beneficial effects that this application can produce include:
[0041] The Ge-based MAX phase cermet provided in this application is a novel 413-type MAX phase. Due to its unique crystal structure of alternating MX and A layers, it combines the excellent characteristics of both metals and ceramics. It possesses excellent mechanical and thermodynamic properties, including a low coefficient of thermal expansion, high bulk modulus, and high elastic modulus. It shows great promise for applications in high-temperature conductive ceramics and low-expansion-coefficient materials, and has significant potential for use in ultra-high-temperature structural components. Its preparation method is a solid-state sintering method, which is simple, yields high-purity products, and requires no large-scale equipment. Attached Figure Description
[0042] Figure 1 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Schematic diagram of the phase crystal structure of 4GeC3.
[0043] Figure 2 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 XRD data of 4GeC3 with multiphase refined spectrum.
[0044] Figure 3 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Scanning electron microscopy morphology and EDS results of 4GeC3. Figure 3 (a) is a SEM image. Figure 3 (b) is a graph of the EDS results.
[0045] Figure 4 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Thermoelectric performance test diagram of 4GeC3. Figure 4 (a) represents the Seebeck coefficient and power factor parallel to the sample direction. Figure 4 (b) Seebeck coefficient and power factor perpendicular to the sample direction.
[0046] Figure 5 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Resistivity test diagram of 4GeC3 sample. Figure 5 (a) is the resistivity parallel to the sample direction. Figure 5 (b) is the resistivity perpendicular to the sample direction.
[0047] Figure 6 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Thermal conductivity test results for 4GeC3 sample. Figure 6 (a) represents the thermal conductivity parallel to the sample direction. Figure 6 (b) represents the thermal conductivity perpendicular to the sample direction.
[0048] Figure 7 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC3Ge-based 413 type high-entropy MAX phase transition temperature XRD pattern.
[0049] Figure 8 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 Temperature-varying XRD full spectrum of 4GeC3Ge-based 413 type high-entropy MAX phase sample.
[0050] Figure 9 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 (a) Temperature dependence of cell parameter a in 4GeC3Ge-based 413-type high-entropy MAX phase samples; (b) Temperature dependence of cell parameter c.
[0051] Figure 10 For (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 The variation of MAX phase bond length with temperature in 4GeC3Ge-based 413 type high-entropy phase bond length.
[0052] Figure 11 In the middle, (a) is (Ti) 0.5 Cr 0.5 (a) is a SEM image of 4GeC3, and (b) is a SEM image of (Ti). 1 / 3 Cr 1 / 3 Mo 1 / 3 SEM image of 4GeC3.
[0053] Figure 12 In the middle, (a) is (Ti) 0.5 Cr 0.5 (a) XRD data of 4GeC3, multiphase refined spectrum, (b) is (Ti 1 / 3 Cr 1 / 3 Mo 1 / 3XRD data of 4GeC3 with multiphase refined spectrum. Detailed Implementation
[0054] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0055] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0056] Unless otherwise specified, all test methods are standard and all instrument settings are those recommended by the manufacturer.
[0057] Example 1
[0058] Ti powder, Cr powder, V powder, Mo powder, Ge powder, and graphite powder with a purity of 99% were weighed in a molar ratio of 1:1:1:1:1:3 and thoroughly ground under an argon protective atmosphere. The uniformly mixed sample was then cold-pressed into discs using a powder press. The resulting discs were placed in a graphite crucible and calcined in a tube furnace. The temperature was first increased to 1000℃ over 200 minutes, then increased to 1615℃ over another 200 minutes, held at 1615℃ for 240 minutes, then decreased to 1000℃ over 120 minutes, then decreased to 400℃ over another 120 minutes, and finally allowed to cool naturally to room temperature to obtain (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC3 sample.
[0059] (Ti) 0.25 Cr 0.25 V 0.25 Mo 0.25 The 4GeC3 sample was thoroughly ground into powder, sieved through a 300-mesh sieve, and then the powder was placed into a graphite mold for discharge plasma sintering at 1300℃ for 10 minutes, with an axial pressure of 35 MPa applied to obtain (Ti). 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC3 bulk material.
[0060] Example 2
[0061] The procedure is the same as in Example 1, except that V powder is not used as the raw material. Instead, Ti powder, Cr powder, Mo powder, Ge powder, and graphite powder with a purity of 99% are used, weighed in a molar ratio of 4 / 3:4 / 3:4 / 3:1:3. Other operations remain unchanged to obtain (Ti1 / 3 Cr 1 / 3 Mo 1 / 3 )4GeC3 bulk material.
[0062] Example 3
[0063] The procedure is the same as in Example 1, except that V powder and Mo powder are not used as raw materials. Instead, Ti powder with a purity of 99%, Cr powder with a purity of 99%, Ge powder with a purity of 99%, and graphite powder with a purity of 99% are used, weighed in a molar ratio of 2:2:1:3. Other operations remain unchanged to obtain (Ti 0.5 Cr 0.5 )4GeC3 bulk material.
[0064] Characterization test
[0065] (Ti) prepared in Example 1 0.25 Cr 0.25 V 0.25 Mo 0.25 The crystal structure of the 4GeC3 sample is as follows: Figure 1 As shown, the Wyckoff site 4e (0, 0, 0.15918) at the M1 position is occupied by three transition metals: Cr, V, and Mo. The Wyckoff site 4f (1 / 3, 2 / 3, 0.05624) at the M2 position is occupied by Ti, V, and Mo. Furthermore, Ge atoms occupy the 2c (1 / 3, 2 / 3, 1 / 4) position, C1 atoms are located at 2a (0, 0, 0), and C2 atoms occupy 4f (2 / 3, 1 / 3, 0.11562). The diffraction patterns were observed using an X-ray diffractometer, and the obtained XRD patterns were refined using Rietveld software with Fullprof software. The results are as follows: Figure 2 As shown, the refined cell parameters The unit cell volume is The obtained refined parameters Rp = 3.62%, Rwp = 5.33%, Rexp = 1.49%, and χ² = 12.8, confirming the reliability of its crystal structure. The refined results demonstrate that the sintered sample possesses the same crystal structure characteristics as most MAX phases, belonging to the P63 / mmc space group (No. 194). (Ti 0.5 Cr 0.5 The multiphase refined XRD data of 4GeC3 is shown in the following figure. Figure 12 As shown in (a), (Ti) 1 / 3 Cr 1 / 3 Mo 1 / 3 The multiphase refined XRD data of 4GeC3 is shown in the following figure. Figure 12 As shown in (b), its cell parameters and cell volume are shown in Table 1.
[0066] Table 1. Cell parameters and cell volume of Ge-based 413-type MAX phase
[0067]
[0068] Its microstructure was observed using a scanning electron microscope (Ti). 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC 3的 Scanning electron microscopy morphology and EDS results are as follows Figure 3 As shown in the figure, a typical layered plate-like stacked structure can be observed, with particle sizes between 20-25 μm. The contents of the four transition metals (Ti, Cr, V, Mo) are 16.5%, 14.2%, 17.2%, and 12.6%, respectively. The atomic contents of these transition metal elements at the M site are nearly equal, with Ge having an atomic content of 12.5%. The ratio of M-site to A-site is close to 4:1, which is consistent with our designed chemical formula. (Ti) 0.5 Cr 0.5 SEM image of 4GeC3 is shown below. Figure 11 As shown in (a), (Ti) 1 / 3 Cr 1 / 3 Mo 1 / 3 SEM image of 4GeC3 is shown below. Figure 11 As shown in (b), a typical layered plate stacking structure can be observed in the figure, with particle sizes between 20-25 μm.
[0069] The (Ti) obtained in Example 1 0.25 Cr 0.25 V 0.25 Mo 0.25 Electrical properties of the 4GeC3 bulk material were tested. The relationships between conductivity and Seebeck coefficient as a function of temperature are shown below. Figure 4 As shown, parallel to the sample direction, the Seebeck coefficient is positive in the low-temperature range (300K-580K), indicating that the dominant charge carrier in the Ge-based 413 high-entropy MAX phase is a hole. As the temperature increases to around 580K, the Seebeck coefficient becomes negative, and the dominant charge carrier type changes from holes to electrons. This transition may be due to electronic excitation within the material or a change in the band structure caused by the increased temperature. At T = 297K, the Seebeck coefficient S = 1.83 mV / K, but this value increases to -4.81 mV / K when the temperature rises to 908K. A larger absolute value of the Seebeck coefficient is obtained perpendicular to the sample direction, along with a relatively high power factor PF, which may be due to factors such as the material's microstructure, grain orientation, or interface effects in the perpendicular direction.
[0070] The (Ti) obtained in Example 10.25 Cr 0.25 V 0.25 Mo 0.25 The resistivity of a 4GeC3 bulk sample was tested, and the results are as follows: Figure 5 As shown, the Ge-based 413-type high-entropy MAX phase sample exhibits weak anisotropy in resistivity. Parallel to the sample direction, the resistivity is 2.9 μΩ·m at room temperature and approximately 3.57 μΩ·m at T = 923 K. Perpendicular to the sample direction, the resistivity is 3.05 μΩ·m at room temperature and approximately 3.57 μΩ·m at T = 923 K. At high temperatures, the resistivity in both directions shows an increasing trend with increasing temperature. This is because with increasing temperature, the thermal vibrations within the material intensify, and the scattering between electrons and the lattice is enhanced, leading to an increase in resistivity, exhibiting metallic properties.
[0071] The (Ti) obtained in Example 1 0.25 Cr 0.25 V 0.25 Mo 0.25 Thermal conductivity tests were conducted on 4GeC3 bulk samples, and the results are as follows: Figure 6 As shown, κ represents two directions. tot κ lat and κ e The curve shows how the total thermal conductivity κ changes with temperature. It can be seen that... tot The thermal conductivity perpendicular to the sample direction remains higher than that parallel to it. The thermal conductivity in both directions increases with increasing temperature, consistent with the variation characteristic of metallic properties. (a) shows the thermal conductivity parallel to the sample direction from 4.86 W·m at room temperature. -1 ·K -1 Increased to 6.43 W·m at 723 K. -1 ·K -1 Electron thermal conductivity accounts for the majority of the thermal conductivity. It gradually increases with increasing temperature. lat / κ tot The value decreased from 90.53(3)% (303K) to 24.61(1)% (723K). This indicates that the electron transport efficiency in the material increases with increasing temperature. (b) shows the thermal conductivity perpendicular to the sample direction, which is 5.89 W·m. -1 ·K -1 (303K), increases to 7.56 W·m at 923K. -1 ·K -1 In the low-temperature range (303K-398K), phonon thermal conductivity is the primary contributor. As the temperature further increases, electronic thermal conductivity becomes dominant. lat / κ totThe value decreased from 142.63 (3)% (303K) to 48.32 (1)% (723K). It is worth noting that thermoelectric characterization requires samples of a certain size and high density. The test samples were prepared in a fast discharge plasma sintering furnace, and high density samples were not obtained. The densities of the two samples were about 85% and 90%, respectively. Therefore, the measured thermal conductivity should be smaller than the actual value.
[0072] The (Ti) obtained in Example 1 0.25 Cr 0.25 Mo 0.25 V 0.25 )4GeC3 bulk samples were subjected to variable-temperature XRD analysis. A Panaco XPert Pro MPD instrument was used to perform variable-temperature XRD analysis on the prepared Ge-based high-entropy MAX phase samples. This diffractometer used a Cu target (K). α1 : K α2 : The tube voltage was 40kV and the tube current was 40mA. The scanning angle range was 5°-95°, the scanning step size was 0.02°, the test temperature was 27℃-1400℃, the heating rate was 5℃ / min, and the variable-temperature XRD test was performed under an argon atmosphere. The height of the sample stage was corrected in real time during the variable-temperature XRD test. The collected variable-temperature XRD patterns are shown below. Figure 7 As shown, the XRD patterns of the sample in the temperature range of 298K-1673K show that no other diffraction peaks appear in the wide temperature range of 298K-1573K. However, at 1673K, as... Figure 8 As shown, additional diffraction peaks were observed at low angles (approximately 20° and 25°). Figure 8 The solid colored line shows the local XRD pattern. The diffraction peaks (102), (104), and (106) shift to lower angles as the temperature increases, indicating that the cell parameters are continuously increasing.
[0073] Rietveld refinement of (Ti) 0.25 Cr 0.25 Mo 0.25 V 0.25 The XRD patterns of 4GeC3 at various temperature points were analyzed to obtain (Ti 0.25 Cr 0.25 Mo 0.25 V 0.25 Cell parameters of the 4GeC3 MAX phase at different temperatures. Figure 9 The figure visually illustrates the trend of cell parameters changing with temperature. As can be seen from the figure, (Ti) 0.25 Cr 0.25 Mo 0.25 V 0.25The cell parameters of 4GeC3 exhibit typical thermal expansion behavior. In the higher temperature range, the cell parameters a and c show an almost linear positive correlation with temperature, consistent with the general laws of thermal expansion. As temperature increases, the vibrational amplitude of atoms in the lattice increases, leading to an increase in lattice spacing and consequently, an increase in cell parameters. The prepared Ge-based 413-type MAX phase (Ti) 0.25 Cr 0.25 Mo 0.25 V 0.25 The thermal expansion coefficient of 4GeC3 is given by the following formula: α = k / l0, where k = k = dl / dT is the slope of the fitted line, l is the cell parameter, and l0 is the cell parameter at room temperature. Therefore, the thermal expansion coefficient along the a and c directions is obtained as α. α and α c The average linear thermal expansion coefficient is determined by α L =(2α) c / α a ) / 3 yields α along the direction a. a =5.20(1)μK -1 α along the c direction c =5.72(4)μK -1 The average linear thermal expansion coefficient α L =5.37(1)μK -1 Thermal expansion anisotropy α c / α α =1.10.
[0074] Based on Rietveld's refinement results, the temperature-dependent variations in the bond lengths of M1-A, M2-M2, M1-M1, M2-C2, M1-M2, M1-C2, and M2-C1 were obtained, as follows: Figure 10 As shown, the bond length increases almost linearly with increasing temperature. However, at 1573 K, d M1-C2 With d M1-M2 The significant fluctuations may be related to a trace amount of phase decomposition at that temperature. Based on the linear fitting results, the thermal expansion coefficients of each bond were statistically analyzed, as shown in Table 2. α M1-A =6.98(3)μK -1 The coefficient of thermal expansion is significantly greater than that of other bonds, indicating that the thermal expansion of this material mainly occurs in the M1-A layer. Furthermore, we observed d M1-C2 The coefficient of thermal expansion is 3.43 (1) μK. -1 (less than d) M2-C2 The coefficient of thermal expansion is 5.72 (3) μK. -1This may be due to the ordered distribution of Ti atoms in the M2 layer and the ordered arrangement of Cr atoms in the M1 layer. Considering that Cr atoms have more valence electrons than Ti atoms, the M1-C2 bond has a relatively stronger binding force, thus causing C2 atoms to be closer to the M1 layer. This is consistent with the results from Rietveld at room temperature.
[0075] Table 2 Thermal expansion coefficients of Ge-based 413 high-entropy MAX phase bonds
[0076]
[0077] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A Ge-based MAX phase cermet, characterized in that, The molecular formula of the Ge-based MAX phase cermet is M4AX3; A represents the element Ge, and X represents the element C. M is a transition metal element, composed of Ti and Cr elements; or M is composed of Ti, Cr, and Mo elements; or M is composed of Ti, Cr, V, and Mo elements.
2. The Ge-based MAX phase cermet according to claim 1, characterized in that, All elements in M are in equal proportions.
3. The Ge-based MAX phase cermet according to claim 1, characterized in that, The Ge-based MAX phase cermet is the 413 phase of the MAX phase system; The Ge-based MAX phase cermet has a hexagonal crystal structure with a space group of P63 / mmc, and the unit cell is composed of three layers of M6X octahedral layers and a single layer of MA triangular prism layers stacked alternately.
4. The Ge-based MAX phase cermet according to claim 1, characterized in that, The molecular formula of the Ge-based MAX phase cermet is (Ti 0.5 Cr 0.5 )4GeC3 or (The 1 / 3 Cr 1 / 3 Mo 1 / 3 )4GeC3 or (The 0.25 Cr 0.25 V 0.25 Mo 0.25 )4GeC3.
5. The method for preparing Ge-based MAX phase cermets according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Weigh the M element powder, Ge element powder and graphite powder in a molar ratio of 4:1:3 and grind them evenly. S2. The uniformly ground powder is cold-pressed into sheets, calcined in an inactive atmosphere, and cooled to room temperature to obtain the Ge-based MAX phase metal ceramic.
6. The preparation method according to claim 5, characterized in that, In the M element powder, the molar ratio of each element powder is equal.
7. The preparation method according to claim 5, characterized in that, The calcination conditions are as follows: heat up to 900-1100℃ in 150-250 minutes, then heat up to 1550-1700℃ in another 150-250 minutes, and hold for 200-300 minutes.
8. The preparation method according to claim 5, characterized in that, It also includes the following steps: S3. Grind the Ge-based MAX phase metal ceramic obtained in step S2 into powder, and perform discharge plasma sintering to obtain Ge-based MAX phase metal ceramic bulk material.
9. The preparation method according to claim 8, characterized in that, The conditions for the discharge plasma sintering are: sintering temperature of 1200-1400℃, sintering time of 8-15min, and application of axial pressure of 30-40MPa.
10. The application of the Ge-based MAX phase metal ceramics according to any one of claims 1 to 4, and the Ge-based MAX phase metal ceramics prepared by the preparation method according to any one of claims 5 to 9, in high-temperature conductive ceramic materials and low expansion coefficient materials.